2005
DOI: 10.1002/pola.21087
|View full text |Cite
|
Sign up to set email alerts
|

Polyimides based on new diamines having pendant imide groups

Abstract: New aromatic diamines were prepared in two steps from 4,5‐dichlorophthalic anhydride and primary amines. The resulting 4,5‐dichlorophthalimide was reacted with 4‐mercaptoaniline, so that the chloroatoms were substituted by the mercapto groups (via the sulfide anions). The new diamines were polycondensed either with the diphenyl ether 3,3′,4,4′‐tetracarboxylic anhydride or with bicyclooctane tetracarboxylic anhydride. These polycondensations were conducted in boiling m‐cresol with azeotropic removal of water. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Polyimides can be prepared by numerous synthetic methods. A comparison of five different methods starting out from free aromatic diamines and tetracarboxylic anhydrides (Scheme ) revealed that direct polycondensation in refluxing (or shortly distilling) m ‐cresol gives the highest M n s 37, 38. The MT mass spectra displayed peaks of circular polyimides up to mass around 13 kDa without any evidence for a “contamination” with linear chains.…”
Section: Kinetically‐controlled Polycondensationsmentioning
confidence: 99%
“…Polyimides can be prepared by numerous synthetic methods. A comparison of five different methods starting out from free aromatic diamines and tetracarboxylic anhydrides (Scheme ) revealed that direct polycondensation in refluxing (or shortly distilling) m ‐cresol gives the highest M n s 37, 38. The MT mass spectra displayed peaks of circular polyimides up to mass around 13 kDa without any evidence for a “contamination” with linear chains.…”
Section: Kinetically‐controlled Polycondensationsmentioning
confidence: 99%
“…However, aromatic polyimides are difficult to process because of their high melting temperature, glass transition temperatures, and poor solubility in organic solvents. It has been reported that incorporating asymmetric6, 7 or bulky groups5, 8, 9–11 into polymers can impart better organo‐solubility because of the decreased packing density and crystallinity. The other benefit of the latter approach is that the T g of polymers can be maintained because of the restricted segmental mobility caused by the bulky pendant.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Polyimides can be prepared by numerous synthetic methods. A comparison of five different methods starting out from free aromatic diamines and tetracarboxylic anhydrides (Scheme 5) revealed that direct polycondensation in refluxing (or shortly distilling) m-cresol gives the highest M n s. 37,38 The MT mass spectra displayed peaks of circular polyimides SCHEME 4 Syntheses of cyclic polyamides by KCPs at low temperatures ( 60 C).…”
Section: Figure 1 Number Fraction Of Rings (N R ) Versus Conversion (P)mentioning
confidence: 99%